Nilai Nasionalisme Sang Proklamator Projek P5 Tema Kearifan Lokal untuk Mendukung Berpikir Kritis Siswa - Makrifah, Arin Nurul; Atmoko, Adi; Anggraini, Ade Eka (BRILIANT: Jurnal Riset dan Konseptual, 2025)
This research aims to 1) develop e-book LKPD, 2) determine the validity of e-book LKPD, 3) analyze the effectiveness of Project P5 e-book LKPD with Local Wisdom Theme in supporting students' critical thinking. Type of development research with the ADDIE model. The development steps consist of 5 stages, namely Analysis, Design, Development, Implementation and Evaluation. The research sample was 29 small group students and 28 large group students. Data was collected through observation, interviews, expert test instruments, and student questionnaires. Qualitative and quantitative data analysis techniques. The results of the research show that the development of the P5 e-book LKPD project with the theme of local wisdom is one contribution to the development of e-book LKPD innovation to support students' critical thinking. Therefore, it can be concluded that the P5 project e-book LKPD with the theme of local wisdom is valid from the validation results of media and material experts, obtaining a percentage of 85% and the percentage of calculation of questionnaire results obtained at 86.64%, so it needs to be developed.